2022
DOI: 10.3390/horticulturae8050352
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of Pear Flower Aroma Characteristics of Seven Cultivars

Abstract: Due to its ornamental and medicinal value, pear flower has been historically loved and used in China. However, the current understanding of their odor-active compounds and aroma profiles is rather limited. This work aimed to evaluate and compare the overall aroma profile of pear flowers; the volatiles in flowers of seven pear cultivars (Anli, Bayuesu, Golden, Brown peel, KorlaXiangli, Lyubaoshi, Xizilü) were analyzed using solid-phase microextraction–gas chromatography-mass spectrometry (SPME-GC-MS). A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Additionally, pollinator abundance was significantly greater on diploid accessions while controlling for floral density, indicating that diploid accessions were disproportionately visited. This may have been due to floral traits not examined here, such as volatile emissions (Kigathi et al, 2019; Li et al, 2022; Rodriguez‐Saona et al, 2011), and therefore should be an area of further research. For farmers, tetraploid cultivars are desirable for their increased persistence and forage yield (Boller et al, 2010), which is beneficial as red clover yield often declines after 3 years (Abberton & Marshall, 2005; Black et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, pollinator abundance was significantly greater on diploid accessions while controlling for floral density, indicating that diploid accessions were disproportionately visited. This may have been due to floral traits not examined here, such as volatile emissions (Kigathi et al, 2019; Li et al, 2022; Rodriguez‐Saona et al, 2011), and therefore should be an area of further research. For farmers, tetraploid cultivars are desirable for their increased persistence and forage yield (Boller et al, 2010), which is beneficial as red clover yield often declines after 3 years (Abberton & Marshall, 2005; Black et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…For example, Li et al (2022) compared the profile of flower odor bouquets among cultivars of P . pyrifolia (‘Golden’, ‘Brown peel’, ‘Xizilü’) by head space SPME-GC-MS [ 42 ]. However, whether the odors of male-fertile/sterile cultivars are different is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have addressed some inter-cultivar differences in odor and nectar of P. pyrifolia. For example, Li et al (2022) compared the profile of flower odor bouquets among cultivars of P. pyrifolia ('Golden', 'Brown peel', 'Xizilu ¨') by head space SPME-GC-MS [42]. However,…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of volatile compounds characterized the quality were strongly influenced by storage conditions, the extraction process, and the climate with the growing condition of the olive [66,[69][70][71]. Previous studies showed that cultivars belong to different horticultural species have a significant effect on biochemical and aroma profile [74][75][76][77][78][79][80][81].…”
Section: Characterization Of Volatile Compoundsmentioning
confidence: 99%